Air Pollution Quotas and the Dynamics of Internal Skilled Migration in Chinese Cities - Bo Yu; Wang-Sheng Lee; Shuddhasattwa Rafiq (Institute of Labor Economics (IZA), 2020)
This paper examines the role of a sulphur dioxide (SO2) emissions quota introduced as part of China's 11th Five-Year Plan on internal movements of high-skilled labour across Chinese prefecture cities. Using data on migration flows calculated through changes in Hukou status, this study suggests that a 1,000 tons increase in the SO2 emissions reduction quota leads on average to approximately a 1.5 percentage points increase in high-skilled net outmigration. Compared to the largest prefectures, this regulation effect is twice as large in the smaller regulated prefectures. A possible mechanism could be that the implementation of SO2 quotas decreases relative labour demand in polluting industries in the regulated cities in the short term, thereby resulting in sectoral transitions from dirty-to-clean industries as well as skilled net outmigration flows. However, this net outmigration trend fades in the long term due to stabilisation in air quality. Our findings help contribute to a broader understanding of the effects of environmental policies on internal labour migration and labour force dynamics.
Keywords: J61; O15; Q53; Q58; 330; air pollution; China; emissions quota; environmental policy; internal migration; sulphur dioxide